A Pharmacovigilance Study Regarding the Risk of Antibiotic-Associated Clostridioides difficile Infection Based on Reports from the EudraVigilance Database: Analysis of Some of the Most Used Antibiotics in Intensive Care Units - Bogdan Ioan Vintila; Anca Maria Arseniu; Claudiu Morgovan; Anca Butuca; Mihai Sava; Victoria Bîrluțiu; Luca Liviu Rus; Steliana Ghibu; Alina Simona Bereanu; Ioana Roxana Codru; Felicia Gabriela Gligor (MDPI AG, 2023)
The Gram-positive anaerobic bacterium Clostridioides difficile (CD) can produce intense exotoxins, contributing to nosocomial infections, and it is the most common cause of health-care-associated infectious diarrhea. Based on spontaneous Individual Case Safety Reports from EudraVigilance (EV), we conducted a descriptive analysis of Clostridioides difficile infection (CDI) cases that reported a spontaneous adverse reaction related to using ceftriaxone, colistimethate, ciprofloxacin, gentamicin, linezolid, meropenem, and piperacillin/tazobactam. Most ADR reports registered in EV that were related to CDI were associated with ceftriaxone (33%), ciprofloxacin (28%), and piperacillin/tazobactam (21%). Additionally, the disproportionality analysis performed showed that all studied antibiotics had a lower reporting probability when compared to clindamycin. A causal relationship between a drug and the occurrence of an adverse reaction cannot be established from EV data alone because the phenomena of underreporting, overreporting, and reporting bias may affect the results. Based on the analysis of the collected data, this study underlines the importance of surveillance and monitoring programs for the consumption of antibiotics. Furthermore, it is essential to use standardized laboratory tests to define CDI's nature accurately. To prevent this infection, specialists should collaborate and adhere strictly to antibiotic stewardship programs, hygiene practices, and isolation protocols.